Synthesis of bis(pentafluorophenyl)azomethine-containing monomers with perfluorinated mono- and biphenylene central nuclei - Kobzar, Ya. L.; Tkachenko, I.M.; Shekera, O.V.; Shevchenko, V.V. (Reports of the National Academy of Sciences of Ukraine, 2015)
New bis(pentafluorophenyl)azomethine-containing compounds, as monomers for the synthesis of core fluorinated polyaryl esters with chromophore groups, are obtained by the interaction of aromatic diamines containing the fragments of tetrafluorobenzene and octafluorobiphenylene with penta- fluorobenzaldehyde. The structure of synthesized monomers was characterized by IR, 1H, and 19F NMR spectroscopy techniques, and their optical properties were studied by UV spectroscopy.